Computer center warehouse management system - Yaseen, Bayan; Iseid, Hiba; Warasneh, Hiba (جامعة بوليتكنك فلسطين - تكنولوجيا المعلومات, 2010)
With the rapid overlapping of information technology in many life aspects ( personal , educational , health , governmental , sports , etc ) , it was normal that a technological academic organization as Palestine Polytechnic University to automate and computerize its different systems . Although the university has already automated a lot of its previous systems such as E - learning , E - registration , E - library , but there still some systems that are working with traditional paper - based method , and one of those systems is the warehouse computer center system . The computer center is responsible for purchasing , installing , maintaining , storing , and distributing all physical hardware and software equipments and networking devices and other related equipments and their distribution at various university buildings and colleges . The staff of the center currently follow - up to the entry , exit , storage , maintenance , warranty period of all these equipments , and transfer from a staff member to another staff member , as well as the transition between the different buildings and inventory , and follow - up warranty matters with the companies through the traditional manual system which suffers from many problems which include : inaccuracies and many potential errors as well as the difficulty of obtaining information about one of the equipment . This project aims to build a modern electronic system to automate all manual processes that currently performed at PPU computer center warehouse . The system will depend on web technology to enable the staff concerned with the system to access it from anywhere and at anytime . The system will help in the archival of all existing equipments in the store and those distributed in the laboratories , offices and various university facilities , as well as issuing various reports in an easily accessible manner through a simple interface .The system also allows browsing equipment specification via mobile phones . The system will be integrated with the existing PPU systems and that requires the use of technology that compatible with other systems , where the technologies will be used are PHP , and MySQL
no of pages 91, 24829, تكنولوجيا المعلومات 18/2010, in the store
Keywords: Computers - systems